Residual Ischemic Risk and Its Determinants in Patients With Previous Myocardial Infarction and Without Prior Stroke or TIA: Insights From the REACH Registry. Issue 11 (2nd September 2016) - Abtan, Jérémie; Bhatt, Deepak L.; Elbez, Yedid; Sorbets, Emmanuel; Eagle, Kim; Ikeda, Yasuo; Wu, David; Hanson, Mary E.; Hannachi, Hakima; Singhal, Puneet K.; Steg, Philippe Gabriel; Ducrocq, Gregory; et al.
Abstract : Background: Although the rate of in‐hospital ischemic events after myocardial infarction (MI) has dramatically decreased, long‐term residual risk may remain substantial. However, most of the information on current residual risk is derived from highly selected randomized trials. Hypothesis: In patients with previous MI and no prior ischemic stroke/transient ischemic attack (TIA), residual ischemic risk increases over time. Methods: Using the international Reduction of Atherothrombosis for Continued Health (REACH) registry, we analyzed baseline characteristics and 4‐year follow‐up of patients with previous MI and no history of stroke/TIA to describe annual rates of recurrent ischemic events globally and by geography. The primary outcome was the composite of cardiovascular death, MI, or stroke. Multivariate analysis identified risk factors associated with recurrent ischemic events. Results: Data from 16 770 patients enrolled at 5587 sites in 44 countries were analyzed. The rate of the primary outcome increased annually from 4.7% during year 1 to reach a 4‐year rate of 15.1%. Compared with North America, Japan experienced lower ischemic event rates ( P < 0.01), whereas Eastern Europe ( P < 0.01) and the Middle East ( P = 0.01) experienced higher ischemic event rates. The presence of congestive heart failure, polyvascular disease, diabetes, atrial fibrillation or flutter, and older age were associated with increased residual risk (all P < 0.01). Statin use was associated with lower ischemic risk ( P < 0.01). Conclusions: In this study, residual ischemic risk after MI accrued progressively up to 4 years of follow‐up, emphasizing the value of intensive secondary prevention strategies to minimize residual risk.